The effects of lithium on ex vivo cytokine production - Rapaport, Mark Hyman; Manji, Husseini K (Biological psychiatry (1969), 2001)
Background: Studies suggest that lithium may have profound immunomodulatory effects in animal models as well as in humans. Methods: In this study, whole blood cultures from normal control subjects were established for 5 days and the effects of lithium on cytokine production were investigated. Because many of lithium’s actions have been postulated to be modulated through phosphoinositide (PI), protein kinase C (PKC) and cyclic adenosine monophosphate (c-AMP) signaling pathways, the effects of myo-inositol and prostaglandin E 2, alone or in combination with lithium, were also investigated. Results: We found that lithium caused an increase in interleukin-4 and interleukin-10 levels, traditionally classified as T-helper lymphocyte type-2 cytokines, and a decrease in interleukin-2 and interferon-γ levels, traditionally classified as T-helper lymphocyte type-1 (TH-1) cytokines. This shift cannot be fully explained by lithium’s actions on the PI, PKC, or c-AMP messenger systems. Conclusions: Monocytes exposed to lithium in the presence of a mitogen for 5 days produced a shift toward the production of TH-2 cytokines and away from the production of TH-1 cytokines. The study suggests that lithium may have complex time-dependent effects on immune function.